Postpartum Mothers' Experiences With Newborn Weight Checks in the Home. Issue 4 (October 2018) - DiTomasso, Diane; Roberts, Mary; Parker Cotton, Brandi
Abstract : Few researchers have examined the perspectives of breastfeeding mothers about using a pediatric scale in the home to monitor infant weight. A cross sectional design was used to measure helpfulness, impact on newborn feeding, and confidence among mothers who used a digital scale to monitor newborn weight. Women ( N = 69) who had given birth in a community hospital in the Northeast region of the United States used a pediatric scale in the home daily for 2 weeks after birth. An online survey determined helpfulness of the scale, if use of the scale impacted feedings, and confidence in breastfeeding. Using a pediatric scale to monitor newborn weight was very helpful ( n = 49; 71%); it was most helpful for primiparous women ( P < .016). Feeding frequency often changed on the basis of neonatal weight ( n = 27; 39%) but only 9% ( n = 6) changed the type of milk fed. Confidence in breastfeeding increased in 90% ( n = 62) of participants. A pediatric scale used in the home to monitor newborn weight is helpful for breastfeeding, especially for primiparous women. Use of the scale may increase maternal confidence in breastfeeding and help guide decisions about feeding frequency.